Physical symptoms as psychiatric manifestations in medical spaces: A qualitative study - Spurrier, Georgia F.; Shulman, Kai; Dibich, Sofia; Benoit, Laelia; Duckworth, Kenneth; Martin, Andrés (Frontiers in Psychiatry, 2023)
Background: Mental health and physical health issues frequently co-occur, but the impact of the psychological wellbeing on the body’s physical functioning remains poorly understood within medical spaces. Individuals living with psychiatric diagnoses in particular are at an increased risk for developing chronic health issues and may be especially disadvantaged by healthcare systems which treat the mind and body as separate entities. Methods: We used secondary analysis (SA) to analyze 30 semi-structured interviews of individuals living with a serious mental illness or reflecting on a family member living with a serious mental illness. We deliberately sampled participants who reflected on salient experiences with co-occurring physical and mental health symptoms. All participants were associated with the National Alliance on Mental Illness (NAMI), the nation’s largest grassroots mental health organization. We coded interviews using qualitative thematic analysis with an interpretative phenomenological framework centered on participants’ subjective experiences. Results: Our analyses uncovered physical health challenges which often occur in individuals living with a psychiatric illness, emphasizing the bidirectionality of mental and physical symptoms. We identified three overarching domains: (i) manifestations, in which participants reflected on how their body responded physically to mental states; (ii) medical management, in which they discussed challenging experiences seeking medical treatment for physical symptoms while living with a mental health condition; and (iii) disjointedness, in which they reflected on challenges in navigating poorly coordinated mental and physical healthcare systems. Discussion: Participants and their medical providers struggled to incorporate mental wellbeing and its impact on physical health into overall healthcare. Given common experiences with misdiagnoses, difficulties navigating health care, and significantly delayed treatment, medical spaces may be able to improve patient experiences and satisfaction by accounting for psychological influences on health outcomes. Conclusions: Greater integration of physical and mental health care in medical spaces could improve health outcomes and reduce challenges for patients seeking treatment.